Unveiling the Digital Impact: Exploring the Influence of Social Media Advertising on Brand Perception - Agarwal, Sugandha; Alami, Rachid (Journal of Ecohumanism, 2024)
Social media advertising is finding its place in brand marketing with each passing day, yet its effect on brand perception is unclear; it is rather blurred. In the present age of digitisation, social media has redefined the way brands connect and communicate with consumers and, at the same time, offers a dynamic ecosystem relating to advertising and brand promotions. The study looks into, through empirical research, the impact of social media advertising on brand awareness and associations, preferences, and loyalty of consumers. The study designed an experiment to expose participants to a randomly assigned brand campaign. In addition, it analysed quantitative survey data and qualitative feedback through ANOVA and thematic analysis, respectively. The findings presented empirical evidence concerning the effectiveness of social media advertising on key brand perception metrics such as brand awareness, associations, preference, and loyalty. The present study will help marketers further hone their social media strategies for maximum returns on investment and more impactful consumer engagement.